Impacts of ISO 9000 on Greek SMEs business performance. Issue 10 (29th November 2018) - Kakouris, Andreas P.; Sfakianaki, Eleni
Abstract : Purpose: The purpose of this paper is to explore the association between ISO 9000 certification and business performance for small-to-medium enterprises in the food and beverage (F&B) industry. Design/methodology/approach: The research employed a qualitative approach based on case studies to investigate in depth how companies perceive ISO 9001. More specifically, four enterprises were examined, and a total of 26 semi-structured in-depth interviews were conducted with top and middle managers from the companies. Questions were validated by experts and through pilot interviews. In total, 45 documents of a broad range related to the quality management system were examined. Personal observation and non-structured consultation with personnel were also used to evaluate the possible impacts and livelihood outcomes. Findings: Research findings showed that the certified companies in the F&B industry gain a number of both internal and external benefits, including: quality awareness, increased productivity, increased personnel participation and efficiency, improved image and penetration into new markets. Regarding the financial benefits of certification, the findings are not as convincing, as one company reported no financial benefits, and the rest reported that financial benefits are indirect and intangible. Conclusively, it can be said that SMEs that wish to pursue certification should certainly expect benefits. Practical implications: Although many studies have concentrated on analyzing the impact of the implementation of ISO 9001 certification, there is still a clear need for research in specific sectors. Practicing managers and researchers will be able to examine findings in order to evaluate benefits and weaknesses from certification, thereby identifying and acting before and after certification. Originality/value: Although the F&B industry has shown a great preference for the ISO 9000 standard and has adopted it extensively, scant empirical evidence has been recorded on the subject. This paper contributes to a better understanding of the benefits for implementing the ISO 9001 certification and to the analysis of its application to the ever-important F&B industry in Greece, a country whose economy is particularly supported by SMEs and has been severely hit by the economic crisis. Researchers will therefore further their knowledge, understand benefits but also acknowledge weaknesses.